Pelagibius marinus sp. nov., a novel bacterium isolated from marine sediment, and emended description of the genus Pelagibius. Issue 4 (22nd April 2022) - Yang, Chen; Zhu, Suting; Sun, Chaoling; Ding, Lijian; Jung, Dawoon; He, Shan; Wang, Ning; Zhang, Weiyan
Abstract : A Gram-stain-negative, rod-shaped, motile and aerobic marine bacterium, designated strain NBU2595 T, was isolated from marine sediment sampled on Meishan Island, located in the East China Sea. Strain NBU2595 T grew at 10–40 °C (optimum, 37 °C), at NaCl concentration of 0–10.0 % (w/v; optimum, 0.5 %) and at pH 6.0–8.0 (optimum, pH 7.0). Catalase and oxidase activities and H2 S production were positive. Methyl red reaction and hydrolysis of casein, starch and Tweens 20, 40, 60 and 80 were negative. The major cellular fatty acids were summed feature 8 (C18 : 1 ω 7 c and/or C18 : 1 ω 6 c ), C18 : 1 2-OH and C18 : 0 3-OH. The sole respiratory quinone was ubiquinone 10. The major polar lipids were phosphatidylglycerol, phosphatidylcholine, phosphatidylethanolamine and phosphatidylmonomethylethanolamine. Comparative analysis of 16S rRNA gene sequences showed highest similarity to Pelagibius litoralis CL-UU02 T (97.9%), and low similarities (<92.9 %) to other species. Phylogenetic analyses indicated that strain NBU2595 T clustered with the genus Pelagibius and was closely related to P. litoralis CL-UU02 T . The average nucleotide identity and digital DNA–DNA hybridization values between strain NBU2595 T and the related species of the genus Pelagibius were well below the thresholds for prokaryotic species delineation. The DNA G+C content was 66.5 mol%. Based on its phenotypic, chemotaxonomic and genotypic data, strain NBU2595 T should be placed in the genus Pelagibius as representing a novel species, for which the name Pelagibius marinus sp. nov. is proposed. The type strain is NBU2595 T (=MCCC 1K04773 T =KCTC 82223 T ).